Heme-based Sensing by the Mammalian Circadian Protein, CLOCK - Lukat-Rodgers, Gudrun S. (2010)
Heme is emerging as a key player in the synchrony of circadian-coupled transcriptional regulation. Current evidence suggests that levels of circadian-linked transcription are regulated in response to both the availability of intracellular heme and by heme-based sensing of carbon monoxide and possibly nitric oxide. The protein CLOCK is central to the regulation and maintenance of circadian rhythms in mammals. CLOCK comprises two PAS domains, each with a heme binding site. Our studies focus on the functionality of the Murine CLOCK PAS–A domain (residues 103-265). We show that CLOCK PAS–A binds Fe(III) protoporhyrin IX to form a complex with 1:1 stoichiometry. Optical absorbance and resonance Raman studies reveal that the heme of ferric CLOCK PAS–A is a six-coordinate, low spin complex whose resonance Raman signature is insensitive to pH over the range of protein stability. Ferrous CLOCK PAS–A is a mixture of five-coordinate, high spin and six-coordinate, low spin complexes. Ferrous CLOCK PAS–A forms complexes with CO and NO. Ferric CLOCK PAS–A undergoes reductive nitrosylation in the presence of NO to generate a CLOCK PAS–A–NO, which is a pentacoordinate FeNO(7) complex. Formation of the highly stable FeNO(7) heme complex from either ferrous or ferric heme makes possible the binding of NO at very low concentration, a characteristic of NO sensors. Comparison of the spectroscopic properties and CO binding kinetics of CLOCK PAS–A with other CO sensor proteins reveals that CLOCK PAS–A exhibits chemical properties consistent with a heme-based gas sensor protein.